Exposing Atlantic Salmon Post-Smolts to Fluctuating Sublethal Nitrite Concentrations in a Commercial Recirculating Aquaculture System (RAS) May Have Negative Consequences - Mortensen, Heidi S.; Jacobsen, Elin; Kolarevic, Jelena; Vang, Amanda (Frontiers in Animal Science, 2022)
Salmon farmers are interested in extending the time post-smolts are reared in recirculating aquaculture systems (RAS). However, there is a lack of knowledge regarding optimal water quality for post-smolts in RAS, and regarding potential consequences of long term exposure to different toxic compounds, such as nitrite, in the RAS water. To address this issue, we conducted a case study at a Faroese Atlantic salmon farm, that rears large post-smolts in fresh water RAS for 22 months before sea transfer, with no additional chloride salt, a known treatment for nitrite toxicity. The aim was to document the potential effects of long-term exposure of fluctuating sub-lethal nitrite concentrations in fresh water RAS on blood physiology of large post-smolts. The study was conducted over six weeks, at the end of the RAS production cycle. Our case study shows that after 22 months in RAS with no additional chloride, the fish had accumulated a plasma nitrite concentration 8 to 16 times higher than the ambient water. Our results indicate that the accumulation may have resulted in extracellular hyperkaliemia, since there was a positive correlation between plasma nitrite and potassium levels (p=0.00095), with potassium levels almost twice as high than previously reported for Atlantic salmon. This could indicate that Atlantic salmon health is challenged due to prolonged sub-lethal nitrite exposure in fresh water RAS. Further research related to long-term nitrite exposure in RAS is needed to asses the potential negative impact, in order to optimize welfare and growth performance during production of Atlantic salmon post-smolts.